What is good and why: the ethics of well - being - Kraut, Richard. 1944- (Harvard University Press, 2009)
"This book Richard Kraut, one of our most respected analytical philosophers, reorients these questions around the notion of what causes human beings to flourish--that is, what is good for us. Observing that we can sensibly talk about what is good for plants and animals no less than what is good for people, Kraut advocates a general principle that applies to the entire world of living things: what is good for complex organisms consists in the maturation and exercise of their natural powers. Drawing on the insights of ancient Greek philosophy, Kraut develops this thought into a good-centered moral philosophy, an "ethics of well-being" that requires all of our efforts to do some good. Even what is good of a kind--good poems no less than good people--must be good for someone. Pleasure plays a key role in this idea of flourishing life, but Kraut opposes the current philosophical orthodoxy of well-being, which views a person?s welfare as a construct of rational desires or plans, actual or ideal. The practical upshot of Kraut?s theory is that many common human pursuits--for riches, fame, domination--are in themselves worthless, while some of the familiar virtues--justice, honesty, and autonomy--are good for every human being.